Liberatory school counseling practices to promote freedom dreaming for Black youth - Mayes, Renae D.; Edirmanasinghe, Natalie; Ieva, Kara; Washington, Ahmad R. (Frontiers in Education, 2022)
The American School Counseling Association (ASCA, 2019), calls for professional school counselors to support the holistic development and success of all students. However, the field of school counseling is riddled with practices that have harmed and dehumanized Black students. For example, school counselors engage in practices (e.g., social emotional learning, vocational guidance, etc.), which work to reinforce white supremacy and dehumanize Black students (Drake & Oglesby, 2020; Love, 2019). Further, school counselors may also contribute to the ways that basic and unique needs of Black students are overlooked, leading to the continued systemic adultification of Black students (Gilmore & Bettis, 2021; Mayes et al., 2021). What is needed is a radical imagination of school counseling, that centers homeplace as the foundation in order to engage in freedom dreaming (hooks, 1990; Kelley, 2003). In this article, authors engage this radical imagination to detail an antiracist view of school counseling practice which embraces freedom dreaming and homeplace through healing and Indigenous educational practices, youth lead school counseling, and critical hip-hop practices to promote joy, creativity, power, love, resistance, and liberation.